Land of the Morning Calm Under the Rising Sun: The Japanese Empire's Efforts to Change Korea's Status from Protectorate to Annexation - Budiarto, Gema (Universitas Diponegoro, 2022)
After succeeding in two battles against the Qing Dynasty, China in 1895 and the Russian Empire in 1905, the Japanese Empire established itself as a powerful nation in the Far East region. After the war ended, the Japanese Empire creates peace treaty with China or the Shimonoseki treaty and Russia or the Portsmouth treaty. All of the treaties touched on the issue of the Korean Peninsula, in which it is clear that the Japanese Empire was making serious efforts for Korean hegemony under the authority of the Japanese Empire. The purpose of this study is to describe the efforts of the Japanese Empire through several treaties that have been made to annex Korean Peninsula. This study used a historical research method consisting of four steps: heuristics, criticism, interpretation, and historiography. The result of this study shows that from 1904 or before the protectorate treaty was signed, the Japanese Empire had violated the Korean neutrality declaration. The protectorate treaty was an attempt by the Japanese Empire to control the international relations of Korea, and in fact that this treaty was not supported by Korea. Meanwhile, in 1910 the Japanese Empire annexed the Korean territory by placing its Governor-General in Korea. <a href=